Innovative Educational Strategies to Increase Online Company Revenue - Ismail, Hariadi; Hasbi, Imanudin; Nugraha, Diki Wahyu; Nugraha, Nugraha; Marbun, Tonggo; Kastanya, Grace (Fakultas Pendidikan Ekonomi dan Bisnis, 2024)
Purpose – The growth of online companies has accelerated in the last decade, however, competition has also become fiercer. To remain profitable and competitive, online companies need to adopt innovative educational strategies that not only attract but also retain customers. This article explores various educational strategies that can help online companies increase their revenue, including customer education, employee training, and community engagement. By utilizing this strategy, online businesses can increase customer satisfaction, improve product usage, and ultimately drive revenue growth. Customer education is one of the key components in this strategy. By providing relevant and useful information about products and services, companies can help customers understand and maximize the benefits of the products they purchase. For example, webinars and tutorials explaining how to use the product can reduce confusion and increase adoption rates. Additionally, informative content such as articles, videos, and FAQs that answer frequently asked questions can improve customer experience and strengthen their loyalty to the brand. Employee training also plays an important role in increasing online company revenues. Well-trained employees can provide better service to customers, which in turn increases customer satisfaction and retention. A comprehensive onboarding program ensures that new employees understand the company's products and services well from the start. Additionally, continuous learning programs that keep employees updated on the latest industry trends and company updates can improve their performance and help companies stay competitive. Community engagement is another effective strategy for increasing online company revenue. By building an online community around a brand, companies can create a sense of community and loyalty among their customers. Online communities allow customers to interact, share experiences, and learn from each other, which can strengthen their relationship with a brand. Additionally, encouraging customers to create and share content related to company products can increase engagement and provide authentic testimonials that can attract new potential customers. Case studies from successful companies such as Duolingo and Salesforce demonstrate the effectiveness of this educational strategy. Duolingo uses gamification and community features to educate and engage its users, while Salesforce offers extensive training and certification programs through its Trailhead platform. Both companies have succeeded in increasing their revenues by prioritizing customer and employee education. Overall, educational strategies are a powerful tool for increasing online company revenue. By educating customers and employees, and building a strong community around the brand, companies can increase customer satisfaction and loyalty, improve product usage, and ultimately drive revenue growth. Further research could explore the specific implementation and impact of these strategies across different types of online companies, as well as identify best practices that could be widely adopted. Design/methods/approach – This research is about Systematic Literature Review (SLR) methodology. The SLR methodology is a structured and comprehensive method for identifying, assessing, and synthesizing literature relevant to a particular research topic. The systematic literature review methodology can be used to review educational strategies in increasing online business revenue.Findings – One effective approach is through implementing educational strategies designed to increase customer engagement and loyalty and improve employee performance. The innovative educational strategies can significantly boost online company revenue by attracting and retaining more users, enhancing their learning experiences, and creating additional streams of income. Research implications/limitations – Through investing in customer education, employee training, and community engagement, companies can increase customer satisfaction, improve product usage, and foster loyalty.Originality/value – The rapid growth of online companies in the last decade has created new opportunities and challenges in the business world. The advent of the internet has changed the business landscape, giving birth to many online companies operating in various sectors. In the midst of increasingly fierce competition, online companies must continue to innovate to remain relevant and profitable